Repair of Y-T humeral fractures in the dog using paired ‘String of Pearls’ locking plates - Ness, M. G. (Veterinary and Comparative Orthopaedics and Traumatology, 2009)
Objectives: To describe a technique for treating Y-T humeral fractures using paired string of pearls (SOP) plates and to review the outcome in 13 cases.Methods: A series of 13 consecutive Y-T humeral fractures, otherwise known as distal humeral dicondylar fractures, were treated according to a surgical protocol which involved combined medial and lateral surgical approaches, accurate reduction and fixation of the condylar fracture with a single transcondylar lag screw, and then re-alignment and fixation of the diaphyseal fracture using two SOP plates and screws.Results: Functional outcome was recorded as excellent in 10 dogs, good in two and poor in one. Six of the 13 patients were working dogs and of these, five returned to pre-injury levels of activity, including work. Complications requiring additional surgery were seen in four of the 13 cases, and three of these cases had a sub-optimal functional outcome.Clinical significance: The results following repair of Y-T fractures using SOP locking plates, placed via combined medial and lateral incisions, compared favourably with those reported for other techniques.
Keywords: Fracture; dog; string of pearls; humeral condyle